Indexing of the 2002 Core Agriculture Serials [Abstract only] - Jodee Kawasaki (Issues in Science and Technology Librarianship, 2004)
This study measures the differences among the major electronic journal article indexes' coverage of the core agricultural literature by using the core agriculture serials list and analyzing where the articles are scanned or indexed.